Skills of the Thought and Academic Performance in university students of the careers of Engineering and Architecture - Arias Barahona Guzmán, Rosario (2018)
The study sought to establish the relationship between the skills of thinking and their factors with academic performance in a group of university entrantsof the careers of engineering and architecture. The total sample was of 113 participants, with whom all the analyzes referring tothinking skills, distribution of factors and levels were carried out.The analysis of the relationship between performance and thinking skills was carried out with 98 participants who counted on the final averages of the ratings. The results show that the participants are distributed mostly in the Normal Lower an3d Normal level and the existence of a moderate positive association with the academic performance. No differences were found according to gender, age and /or specialty.